1979
DOI: 10.1172/jci109485
|View full text |Cite
|
Sign up to set email alerts
|

Micropuncture determination of pH, PCO2, and total CO2 concentration in accessible structures of the rat renal cortex.

Abstract: A B S T R A C T Previous studies evaluating the mechanism of renal HCO-reabsorption have assumed equilibrium between systemic arterial blood and tubular fluid Pco2. We have recently reported that the Pco2 in proximal and distal tubular fluid as well as the stellate vessel significantly exceeded arterial Pco2 by 25.9 +0.92 mm Hg. The purpose of this study was to determine directly, for the first time, pH, Pco2, and total CO2 concentration in the accessible structures of the rat renal cortex with both microelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 26 publications
5
40
0
1
Order By: Relevance
“…Moreover, a reduction in RBF is only one possible explanation for the higher Pco2 values. Recent work has implicated chemical disequilibrium between C02 and HCO3 in the renal vasculature and vascularvascular exchange of C02 as factors contributing to the high Pco2 in the renal cortex (16,17). Whether these factors contribute to the differences in cortical Pco2 between control and CMA rats remains a subject for future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a reduction in RBF is only one possible explanation for the higher Pco2 values. Recent work has implicated chemical disequilibrium between C02 and HCO3 in the renal vasculature and vascularvascular exchange of C02 as factors contributing to the high Pco2 in the renal cortex (16,17). Whether these factors contribute to the differences in cortical Pco2 between control and CMA rats remains a subject for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The loops were confirmed as being the last accessible proximal convolutions by the failure of a small injected oil droplet to reappear in any subsequent proximal loop on the surface of the kidney. Timed collections (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Pco2 measurements. The Pco2 microelectrodes used in these studies were constructed as described previously (8), and had outer tip diameters of [4][5][6][7][8][9][10] The ability of our microelectrode system to detect small differences in Pco2, with the recorder set at 1 mV = 5 mm, was tested by using it to measure Pco2 in three solutions equilibrated with known gas mixtures (Pco2 values of 30.9, 32.4, and 35.9 mmHg as determined by Scholander analysis).…”
Section: Methodsmentioning
confidence: 99%
“…30 The luminal pH is highly acidic in the medullary ray and at the outer stripe of the outer medulla, where the straight portion of the proximal tubule (S3) is located. [35][36][37][38][39] Importantly, a detailed histologic analysis revealed that 8-OHdG-ir cells were concomitantly distributed around the medullary ray and at the outer stripe of the outer medulla. Consistent with this observation, the histochemical analysis using LTL as well as the flow cytometric analysis using an anti-CD13 antibody demonstrated that albuminuria-induced oxidative stress was prominent in proximal tubular cells.…”
Section: Effect Of Luminal Alkalinization On Protein-overload Nephropmentioning
confidence: 99%
“…35,36 Furthermore, another report showed that the pH of the distal portion of proximal tubule was even lower, i.e., pH 6.2, in acidotic rats. 37 However, the pH level that was directly determined in those studies was measured only at accessible superficial sites (S1 and S2).…”
mentioning
confidence: 99%
“…The reason for this pH dependence may reside in the fact that the protonated form of ferryl heme (Fe(IV)OH Ϫ ) is the reactive species, which is formally equivalent to a hydroxyl radical coordinated to ferric heme. It is important to note that renal tubular fluid is relatively acidic and the pH of the surrounding interstitium decreases further during low blood flow states (41). Thus, MetMb deposited in the renal tubules is in a milieu that greatly promotes the ability of Mb to induce lipid peroxidation.…”
Section: Effect Of Alkalinization On the Stability Of Ferryl-mb And Cmentioning
confidence: 99%